NUTRITIONAL STATUS OF ADOLESCENTS OF DANKANDE COMMUNITY OF KADUNA METROPOLIS - Abdullahi, H.; Anigo, M. K.; Owolabi, A. O.; Alhassan, U.; Sallau, A. B.; Awal, M. I.; Abubakar, Y. S.; Saliu, M. A.; Hassan, S. M.; Jajere, U. M.; Luka, J. (FUDMA JOURNAL OF SCIENCES, 2021)
Studies on the nutritional status of adolescents in Dankande community of Kaduna metropolis were carried out. Adolescence is a period between 10 to 19 years of age. This period is a critical period where a healthy diet is needed for proper growth, development, academic performances and human capital development. A validated semi-structured questionnaire was used to assessed socio-demographic characteristic of the adolescent caregivers and dietary pattern of the adolescent while weight, height and BMI were used to assess the anthropometry indices of adolescent. 37.2% of adolescents were between age 10-14 years while 62.8% were between 15-19 years. Also, 5.1% of the adolescents were married, 88.5 were single and 6.4% windowed. (19.2%) of adolescents has no formal education, (2.6%) completed primary school, (29.5%) uncompleted primary school, (2.6%) completed Junior Secondary School, (19.2%) uncompleted Junior Secondary School, while (1.3%) completed Senior Secondary and (25.6%) did not complete Senior Secondary respectively. However, on average (35.9%) of adolescent were dieting and (64.1%) were not dieting while (32.1%) were concerned about their weight and (67.9%) were not concerned about their weight. Few adolescents were losing control of their weight (24.4%) while the majority had their weight in check (75.6%), they engaged in physical activity (85.9%), while many adolescents spent more than two hours per day watching tv/games (69.2%). 17.9% engage in smoking while (5.1%) are involved in drinking alcohol, beer or wine. The nutritional status of adolescents of Dankande community of Kaduna state (56.4%) is good when compared with the national average